Pemanfaatan Odoo Untuk Implementasi HRIS Di Perusahaan Roti Menggunakan Metode ASAP - Nurlela, Ida; Yulhendri, Yulhendri (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The importance of information technology in the advancement of human resource carriers is gaining momentum in the era of globalization and rapid technological developments today. The impact of information technology on the business environment has resulted in significant changes in the management of human resources in organizations. In the HRD system in a bread flour company, the management of each HRD business process is still done manually using paper as a document and for data storage using Ms. Excel, where HRD still has difficulty in managing employee data. With the method using BPMN, the HRD system business process can be analyzed, and the ASAP method for HRD system optimization using Odoo, the purpose of the study using odoo every business process starting from recruitment, absence, leave, orientation and training, and payroll will facilitate the HRD system in the company because each module is integrated, and data storage already uses a database. Then the results of this study after going through the User Acceptance Testing process using the Black Box Testing technique, the researcher can conclude that the use of Odoo to optimize the HRD system used passes functionally with several notes regarding user access rights that must be adjusted to the jobdesk of each employee.